Recreational terror : women and the pleasures of horror film viewing - Pinedo, Isabel Cristina, 1957- (SUNY series, interruptions--border testimony(ies) and critical discourse/s., 1997)
In Recreational Terror, Isabel Cristina Pinedo analyzes how the contemporary horror film produces recreational terror as a pleasurable encounter with violence and danger for female spectators. She challenges the conventional wisdom that violent horror films can only degrade women and incite violence, and contends instead that the contemporary horror film speaks to the cultural need to express rage and terror in the midst of social upheaval.